How Servant Leadership Sparks Feedback-Seeking Behavior: A Moderated Mediation Model - Qin, Dong; Xu, Yan; Li, Chaoping; Meng, Xue (Frontiers in Psychology, 2021)
Drawing upon social information processing theory, we propose that moqi with supervisors mediates the relationship between perceived servant leadership and follower feedback-seeking behavior. Subordinates’ traditionality plays a moderating role in this process. Using a sample of 440 Chinese working adults, correlation analyses, mediation analysis, and moderated mediation analysis was performed through R and SPSS PROCESS Macro. The results revealed that servant leadership positively correlates with employees’ feedback-seeking behavior via moqi with supervisors. Moreover, these indirect effects of servant leadership were moderated by traditionality, such that servant leadership had weaker relations with feedback-seeking behavior when traditionality was higher (vs. lower). Theoretical and practical implications and limitations of the study, and suggestions for further study were discussed.